Facial emotion recognition abilities of individuals with schizophrenia and the influence of parental bonding—An exploratory study in a forensic sample - Salome Todua-Lennigk; Gunnar Deuring; Marc Graf; Henning Hachtel (PLoS ONE, 2026)
Individuals diagnosed with schizophrenia experience cognitive impairments, including a decline in social cognition, which encompasses facial emotion recognition. Facial emotion recognition is an important aspect of social interaction, guiding people’s actions and influencing their social functioning. Early childhood experiences, such as parental attachment, are one of the most influential factors in the development of many psychiatric symptoms including impairment of social cognition. Our aim was to explore this poorly researched area. We investigate the hypothesis that dysfunctional parenting styles negatively affect facial emotion recognition abilities in general and further worsen these deficits in individuals diagnosed with schizophrenia. A total of 32 participants were included in an exploratory study, comprising 16 patients with paranoid schizophrenia recruited from forensic clinics in Switzerland, and 16 age and education matched healthy controls without history of psychiatric or neurological illnesses. Parental attachment was assessed using the Parental Bonding Inventory and subjects were assigned to subgroups of optimal vs. neglectful parenting style from both parental sides. Facial emotion recognition was operationalized as the error rate in an emotion-naming task using standardized images of the five basic emotions. Overall, schizophrenia patients made significantly more errors in the facial emotion recognition task than healthy controls. Interestingly, in the subgroup with optimal parental attachment experiences, patients did not significantly differ from controls, whereas in cases of neglectful parenting, the patients showed a much higher error rate in facial emotion recognition compared to healthy controls ( p < .001), as well as compared to patients with optimal parenting experience ( p < .01). Neglectful parenting appears to exacerbate the adverse effects of schizophrenia on facial emotion recognition; i.e., optimal parenting might mitigate deficits caused by schizophrenia spectrum disorder patients and help compensate for FER impairments.